Kewibawaan Guru PAI dalam Mengembangkan Soft Skill Siswa di SMP IT Nurul Ilmi Deli Serdang - Lestari, Armita Dwi; Dahlan, Zaini; Srdianti, Siti (CV. PUSDIKRA MITRA JAYA, 2024)
This study aims to examine the authority of PAI teachers in developing students' soft skills at SMP IT Nurul Ilmi Deli Serdang. The authority of PAI teachers is a crucial aspect that can influence a student's character building and social skills which include the ability to communicate, teamwork, time management, and critical thinking. Therefore, the authority of PAI teachers is a very important aspect that can affect the formation of students' character and social skills. The research method used is descriptive qualitative research method with data collection techniques through interviews, observation, and documentation. The subjects of this study consisted of PAI teachers, students, principals, and vice principals. The results of the study have shown that PAI teachers at SMP IT Nurul Ilmi Deli Serdang have high authority which can be seen from how they teach, are able to provide role models, and guide and direct students. Authoritative teachers can create a conducive environment, and inspire students to behave positively. The implications of this study indicate that increasing the authority of PAI teachers through training and professional development is very important to support the progress of character education. It can be concluded that the authority of PAI teachers is a key factor in developing students' soft skills, which in turn will contribute to the formation of strong character among students.